Biscuit meal composition in pig feeding - Corassa, Anderson (Comunicata Scientiae, 2014)
This study was conducted to compile results of the nutritional composition of the biscuit meal from14 papers from studies published in journals and reports during 2000 and 2011 to characterize thegross, digestible and metabolizable energy (DE and ME, kcal / kg) for pigs, dry mater (DM), crudeprotein (CP), ether extract (EE), mineral matter (MM), crude fiber (CF), calcium (Ca), phosphorus(Pt), sodium (Na), total lysine (LIS), methionine plus cystine total (MC), threonine (THR), tryptophan(TRI) and non-nitrogen extraction (ENN) of this product. The mean values were biscuit meal 3681 kcal/ kg; 8.93%, 9.07%, 11.61%, 2.71%, 2.64%, 0.12%, 0.21%; 0, 34%, 0.23%, 0.30%, 0.26%, 0.16% and 69.66%,for ME; U, CP, EE, MM, FB; Ca, Pt, Na; LIS; MC , TRE, TRI and NFE, respectively.